2005
DOI: 10.1007/s11373-005-3008-x
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol prevents cardiac hypertrophy and overexpression of hypoxia-inducible factor-1α and vascular endothelial growth factor in pressure-overloaded rat heart

Abstract: The use of beta-blockers has emerged as a beneficial treatment for cardiac hypertrophy. Hypoxia-inducible factor-1alpha (HIF-1alpha) is tightly regulated in the ventricular myocardium. However, the expression of HIF-1alpha in cardiac hypertrophy due to pressure overload and after treatment with beta-blocker is little known. To evaluate the effect of carvedilol on both myocardial HIF-1alpha expression and cardiac hypertrophy, infra-renal aortic banding was performed for 4 weeks in adult Sprague-Dawley rats to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 28 publications
5
51
0
2
Order By: Relevance
“…Consistent with previous results, 29,30 TAC led to a 2.9-fold (PϽ0.01) increase in VEGF-A transcript expression ( Figure 1A). To investigate the links between coronary vasculature and compensatory cardiac hypertrophy, an adenoviral vector encoding a decoy VEGF receptor fused to the Fc fragment of IgG2a (Ad-Flk) or a control vector expressing only the Fc fragment (Ad-cont) was delivered to mice, and hearts were subjected to sham surgery or pressure overload resulting from TAC.…”
Section: Vegf Receptor Decoy Reduces Capillary Density In Hearts Subjsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous results, 29,30 TAC led to a 2.9-fold (PϽ0.01) increase in VEGF-A transcript expression ( Figure 1A). To investigate the links between coronary vasculature and compensatory cardiac hypertrophy, an adenoviral vector encoding a decoy VEGF receptor fused to the Fc fragment of IgG2a (Ad-Flk) or a control vector expressing only the Fc fragment (Ad-cont) was delivered to mice, and hearts were subjected to sham surgery or pressure overload resulting from TAC.…”
Section: Vegf Receptor Decoy Reduces Capillary Density In Hearts Subjsupporting
confidence: 92%
“…Previous studies have shown that VEGF is upregulated in myocardium in pathological conditions such as myocardial infarction, 31,32 pressure overload, 29,30 and hemodynamic overload. 33 In vitro, it has been shown that VEGF is secreted from cardiomyocytes in response to various extracellular stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been extensively studied regarding its effect on cell growth and proliferation. In the cardiomyocytes, VEGF also is required for cell growth [22][23][24]. Studies in vivo have shown that a decoy VEGF receptor blocked cardiac growth induced by Akt1 activation [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…This decreased vascularity in hypertrophic myocardium is exacerbated by increases in myocyte size and tissue fibrosis, which increase diffusion distances and decrease oxygen availability to myocytes (and perhaps more importantly, their mitochondria) [27,28]. While up-regulation of hypoxia inducible factor HIF-1α is increasingly being recognized as an important instigator of cardiac hypertrophy [29][30][31] and mediator of decline into heart failure [32][33][34], we have found no reports that successfully demonstrate non-invasive measurement of hypoxia itself in hypertrophic or failing myocardium. As we shall discuss, this is most probably because most existing approaches designed to assess tissue hypoxia have insufficient sensitivity to detect the less extreme levels of hypoxia that are likely to be involved.…”
Section: Potential Applications Of Cardiac Hypoxia Imagingmentioning
confidence: 99%
“…Since the main mediator of hypoxic injury in the pathogenesis of cardiac hypertrophy is upregulated HIF-1α expression, HIF-1α up-regulation would seem to be the most appropriate parallel biomarker to target [29][30][31].…”
Section: Requirements Of An Ideal Cardiac Hypoxia Imaging Agentmentioning
confidence: 99%